Validation of the Measuring Protocol for the Infraspinatus Muscle with M-Mode Ultrasound in Asymptomatic Subjects. Intra- and Inter-examiner Reliability Study - Marina Ortega-Santamaría; María-Eugenia Torralbo-Álvarez-Novoa; Juan-Nicolás Cuenca-Zaldívar; Fermin Naranjo-Cinto; Samuel Fernández-Carnero; Daniel Pecos-Martín (Diagnostics, 2023)
M-mode ultrasound is a reliable and valid instrument for assessing muscle activity. However, it has not been studied in any of the muscles belonging to the shoulder joint complex, particularly in the infraspinatus muscle. The aim of this study is the validation of the infraspinatus muscle activity measurement protocol with the M-mode ultrasound in asymptomatic subjects. Sixty asymptomatic volunteers were evaluated by two physiotherapists who were blinded; each of them carried out three measurements with the M-mode ultrasound in infraspinatus muscle and analysed the muscle thickness at rest and contraction, velocity of muscle activation and relaxation and Maximum Voluntary Isometric Contraction (MVIC). Intra-observer reliability was significant in both observers, showing good thickness at rest (ICC = 0.833–0.889), thickness in contraction (ICC = 0.861–0.933) and MVIC (ICC = 0.875–0.813); moderate in the activation velocity (ICC = 0.499–0.547) and relaxation velocity (ICC = 0.457–0.606). The inter-observer reliability also had good thickness at rest (ICC = 0.797), thickness in contraction (ICC = 0.89) and MVIC (ICC = 0.84); poor in relaxation time variable (ICC = 0.474) and not significant at the activation velocity (ICC = 0). The muscle activity measurement protocol of the infraspinatus muscle measured with M-mode ultrasound has been found to be reliable in asymptomatic subjects, for both the intra-examiner and inter-examiner.